2010
DOI: 10.1021/ja106901u
|View full text |Cite
|
Sign up to set email alerts
|

Cyano Diels−Alder and Cyano Ene Reactions. Applications in a Formal [2 + 2 + 2] Cycloaddition Strategy for the Synthesis of Pyridines

Abstract: Two metal-free, formal [2 + 2 + 2] cycloaddition strategies for the construction of polycyclic pyridine derivatives are described that proceed via pericyclic cascade mechanisms featuring the participation of unactivated cyano groups as enophile and dienophile cycloaddition partners.The nitrile functional group rarely participates as an enophile or dienophile in Alder ene and Diels-Alder cycloadditions.i , ii Herein we describe two formal [2 + 2 + 2] strategies for the synthesis of substituted pyridines that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 21 publications
(13 reference statements)
0
36
0
1
Order By: Relevance
“…In the first, Danheiser et al described a formal, metal-free [2 + 2 + 2] cycloaddition to form pyridines that takes place by a propargylic ene reaction, furnishing a vinylallene that subsequently participates in a Diels−Alder reaction with a tethered cyano group. 11 In the other, Mukai et al describe a rhodium(I)-catalyzed intramolecular carbonylative [2 + 2 + 1] cycloaddition (aza-Pauson−Khand type reaction) of allenenitrile substrates. 12 It should be noted that the authors postulate a mechanism in which the nitrile does not directly participate in the reaction but rather isomerizes to a ketenimine, which enters the catalytic cycle.…”
mentioning
confidence: 99%
“…In the first, Danheiser et al described a formal, metal-free [2 + 2 + 2] cycloaddition to form pyridines that takes place by a propargylic ene reaction, furnishing a vinylallene that subsequently participates in a Diels−Alder reaction with a tethered cyano group. 11 In the other, Mukai et al describe a rhodium(I)-catalyzed intramolecular carbonylative [2 + 2 + 1] cycloaddition (aza-Pauson−Khand type reaction) of allenenitrile substrates. 12 It should be noted that the authors postulate a mechanism in which the nitrile does not directly participate in the reaction but rather isomerizes to a ketenimine, which enters the catalytic cycle.…”
mentioning
confidence: 99%
“…[18] The reactions of both arylacetylene-and alkylacetylene-derived dienynes 1 l-n furnished vinyl-substituted 1,4-dihydronaphthalenes 9 l-n in good yields (Table 3, entries 2-4). [20] In the case of dienynes that possess a tertiary propargyl ether moiety, the carbonyl migration reaction proceeds via intermediates B, C, A, and D to afford rhodium carbonyl hydride E. However, we could not observe the formation of dienal 4, and so the direct formation of intermediate E from intermediate C is more likely. A plausible mechanism for the present cascade reactions is outlined in Scheme 5.…”
Section: Methodsmentioning
confidence: 65%
“…A triyne or ene/diyne precursor undergoes a thermal cyclisation when subjected to microwave radiation to afford a tricycle with a tetrasubstituted benzene core (Scheme ) . Sakai and Danheiser extended this work to include the use of nitriles, hence forming a pyridine derivative …”
Section: Methodsmentioning
confidence: 99%
“…[8] Sakai and Danheiser extended this work to include the use of nitriles, hence forming ap yridine derivative. [9] Parsons and co-workers have demonstrated that at hermal intramolecular cyclisation can be used to form the lactonamycin core and other interesting fused heterocyclic and carbocy-clic compounds without the use of metal catalysis. [10] Further,i t was found that in general, ene-diynes can cyclise to afford furans and dihydrofurans.…”
mentioning
confidence: 99%